Environmental Legality and Justice: Assessing Mining Business Permits in Indonesia’s Vulnerable Coastal and Small Islands - Risman Setiawan (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2026)
Regulatory inconsistencies between the Mining Law and the Coastal and Small Islands Law have created legal uncertainty regarding the issuance of Mining Business Permits in coastal areas and on small islands. This normative legal study utilizes statutory, case-based, and conceptual approaches to assess the legal validity of these permits under Indonesia’s environmental laws. The findings indicate a conflict of norms, as Mining Business Permits (IUPs) are frequently granted for islands smaller than 2,000 km², despite explicit prohibition under the PWP3K Law and subsequent Supreme Court decisions upholding the principle of Green Justice. The centralization of licensing authority following amendments to the Mining Law has diminished ecological oversight and often neglects zoning plan instruments (RZWP3K) and the participation rights of local communities. The study concludes that the validity of mining permits should not depend solely on formal administrative criteria but must also satisfy ecological legality standards to ensure the protection of coastal and small island environments. These findings underscore the need for the government to conduct a comprehensive legal audit and harmonize sectoral regulations to guarantee legal certainty, ecological justice, and the protection of coastal communities’ constitutional rights to a healthy environment.